The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5296/ijl.v4i2.1707
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Metacognitive Strategy Instruction on the Listening Performance of EFL Students

Abstract: The aim of this study is to explore the effect of metacognitive strategy instruction on the listening performance of EFL university students. The participants were 82 students studying English translation and literature at Shahid Beheshti University. After screening the participants, 62 of them were selected and assigned to experimental and control groups. The experimental group (n=32) received the strategy training following the models proposed by Vandergrift and Tafaghodtari (2010) and O'Malley and Chamot (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
3
22
0
3
Order By: Relevance
“…It was concluded that the strategy instruction within test procedures has significant effects on the listening comprehension ability of the EFL learners. Our results noting of success of strategy instruction in the study are in line with the outcomes of a number of studies in which strategy instruction was attempted and proved statistically significant (Birjandi & Rahimi, 2012;Carrier, 2003;Vandergrift, 1997).…”
Section: Discussionsupporting
confidence: 76%
“…It was concluded that the strategy instruction within test procedures has significant effects on the listening comprehension ability of the EFL learners. Our results noting of success of strategy instruction in the study are in line with the outcomes of a number of studies in which strategy instruction was attempted and proved statistically significant (Birjandi & Rahimi, 2012;Carrier, 2003;Vandergrift, 1997).…”
Section: Discussionsupporting
confidence: 76%
“…This effective way of Explicit M-CCSI is relevant with Field's statement that between metacognitive and cognitive strategy instruction cannot be separated (Field, 2008). Furthermore, generally, the significant effect of the listening strategy instruction on students' listening proficiency is corroborated by some studies (Amin, 2011;Selamat & Sidhu, 2013, Birjandi & Rahimi, 2012Hariri, 2014;Guan, 2014).…”
Section: Theory and Practice In Language Studiesmentioning
confidence: 52%
“…As for Fahim and Fakhri's (2014) study, there are several issues which are indicative of misunderstandings also variously apparent in other related research articles (e.g., Birjandi & Rahimi, 2012;Bozorgian, 2012;Rahimi & Katal, 2013). First, Fahim and Fakhri refer to metacognitive strategy instruction as a form of metacognitive instruction in their article (e.g., pp.…”
Section: Fahim and Fakhri (2014)mentioning
confidence: 84%
“…Regarding the Vandergrift and Tafaghodtari () study, Birjandi and Rahimi (, p. 498), and Movahed (, p. 88), for example, suggest that Vandergrift and Tafaghodtari present a model of strategy instruction in their article. Vandergrift and Tafaghodtari's presentation and coverage of the stages and metacognitive processes (modified from Vandergrift, ) in the pedagogical approach employed (see p. 475) at no point refers to it as being a model of strategy instruction.…”
Section: Sample Studiesmentioning
confidence: 95%